Characteristics and patterns of marine debris in the Chinese beach-sea continuum - Ouyang, Xiaoguang; Yang, Zhifeng (Frontiers in Marine Science, 2022)
The amounts of marine debris and plastic pollution have been growing dramatically in the environment. Floating marine debris can be transported between the sea and coastal zone by various processes. However, it remains unknown if marine debris in the sea and coastal zone are quantitatively related. This study collected time-series data on marine debris (including plastics) from China’s beaches and adjoining seas over a 10-year period (2012–2021). It aims to investigate (1) the characteristics of debris distribution in the beach-sea continuum, (2) the relationships among the density and accumulation density of marine debris on beaches, sea surfaces and seafloors. Our results show that the density of marine debris and plastics on beaches and seafloors in the pandemic period were 3–5 folds of those in the pre-pandemic period. The density (104682.4 ± 27793.0 items km–2) and accumulation density (1787.4 ± 220.0 kg km–2) of marine debris on beaches were significantly higher than those on both sea surfaces (3320.8 ± 446.0 items km–2 and 21.6 ± 5.7 kg km–2) and seafloors (2453.7 ± 868.4 items km–2 and 117.5 ± 70.4 kg km–2). The density of plastics on beaches (85373.0 ± 21633.8 items km–2) was significantly higher than that on sea surfaces (2915.4 ± 365.8 items km–2) and seafloors (2254.2 ± 717.1 items km–2). The density of small-to-medium (0–10cm) floating debris (3419.5 ± 418.2 items km–2) was more than 100 times higher than the density of large (> 10cm) floating debris (29.6 ± 3.1 items km–2). The proportion of plastics in marine debris on sea surfaces (83.3 ± 1.3%) was significantly higher than that on beaches (74.1 ± 2.5%) but not significantly different from that on seafloors (81.1 ± 3.0%). There are significant relationships between the density of debris on seafloors and that on beaches, between the density or accumulation density of debris on seafloors and that on sea surfaces. This study suggests that the density and accumulation density of marine debris on seafloors were closely associated with those on sea surfaces and beaches. The results can help to estimate the transportation, deposition and aggregation of marine debris from beaches and sea surfaces to seafloors.